The burning glass : a play - Morgan, Charles (London : Macmillan, 1954)
National Theatre, The Theatre Guild and John C. Wilson present Cedric Hardwicke in "The Burning Glass," a new play by Charles Morgan, with Walter Matthau, Isobel Elsom, Scott Forbes, and Maria Riva, staged by Luther Kennett, setting by Oliver Smith, costumes by Noel Taylor, lighting by John Davis.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: English Play; Theater programs -- Washington (D.C.); Theater programs -- 1954.